Reliable Multistate RRAM Devices for Reconfigurable CAM and IMC Applications - Shengpeng Xing; Zijian Wang; Zhen Wang; Pengtao Li; Xuemeng Fan; Ziyang Zhang; Guobin Zhang; Jianhao Kan; Qi Luo; Shuai Zhong; Yishu Zhang (IEEE Journal of the Electron Devices Society)
This work presents a reliable multistate RRAM device based on a Cu/Ta2O5/WO ${}_{\text {3-x}}$ /Pt structure, utilizing fully CMOS-compatible materials. The device demonstrates four distinct resistive states under varying switching voltages, achieving a swift response time of 25 ns and an on/off ratio exceeding $10{^{{4}}}$ . Additionally, it demonstrates a robust data retention time exceeding $10^{6}$ seconds and endures more than $10^{4}$ pulses in endurance tests. Statistical analysis conducted over 100 cycles across ten devices reveals consistent resistance characteristics, with variations maintained below 10%. Leveraging these advantages, the RRAM devices were integrated with MOS transistors to construct a 4T2R unit-based array, enabling reconfigurable applications such as analog voltage-based content-addressable memory (CAM) and in-memory computing (IMC) accelerators. Notably, the proposed solution reduces energy consumption by over 20% in CAM applications and significantly enhances energy efficiency for fingerprint recognition tasks through convolution operations, achieving more than three times the energy efficiency compared to conventional GPU and CPU systems while maintaining an accuracy of 98%.